1992
DOI: 10.1093/bja/68.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Reported Significant Observations During Anaesthesia: A Prospective Analysis Over an 18-Month Period

Abstract: We describe a prospective analysis, in one hospital, of reported significant observations involving unsafe practices and working conditions during anaesthesia. Of the 549 significant observations reported voluntarily during a period of 18 months, 82% involved occurrences which were considered preventable and 27% could have been fatal if they had not been recognized and corrected. Ninety-three percent of incidents did not lead to a negative outcome. Human error was responsible for 411 (75%) reports. Lack of vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 10 publications
2
40
0
3
Order By: Relevance
“…After these strategies are in place it is necessary to assess their effectiveness [8]. It has also been suggested that even in the case of heterogeneous results, targeting high priority areas could decrease the overall frequency of events [16].…”
Section: Discussionmentioning
confidence: 99%
“…After these strategies are in place it is necessary to assess their effectiveness [8]. It has also been suggested that even in the case of heterogeneous results, targeting high priority areas could decrease the overall frequency of events [16].…”
Section: Discussionmentioning
confidence: 99%
“…Critical incident reporting is a well established QA in clinical anaesthesia [1][2][3][4][5][6]. However, there are significant differences regarding patient management between the operating theatre and the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Despite major advances in staff training and patient monitoring, appreciable morbidity and mortality attributable to mishaps still occur. Critical incident reporting is well established in anaesthesia [1][2][3][4][5][6] and several studies have now been published which highlight the role of both active and latent errors in the genesis of critical incidents. Until recently, little information was available regarding critical incidents [7][8][9][10][11] occurring in critically ill patients in the ICU especially when technically sophisticated procedures are performed on acutely ill patients with unstable physiology.…”
mentioning
confidence: 99%
“…Item error weighting was defined as follows: Weighting: 1) No risk: an incident without any potential risk for the patient; 2) Low risk: an incident which could have led to reversible damage to the patient; 3) Medium risk: an incident which could have led to irreversible damage to the patient; and 4) High risk: a potentially fatal incident. 6 Once the checklists were returned, they were anonymously collated and emailed back to the participants in round 2. Participants were then asked to check off whether the item should remain or be deleted, and to assign a weighting if it was a new item to them or re-assign a weighting if deemed appropriate.…”
Section: Methodsmentioning
confidence: 99%